1991
DOI: 10.1002/jor.1100090313
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage exposure to polymethyl methacrylate leads to mediator release and injury

Abstract: To understand further the role of macrophages in the loosening of cemented arthroplasty, several in vitro effects of polymethyl methacrylate (PMMA) particle exposure in these cells were studied. The kinetics of arachidonic acid and derived inflammatory mediator release was characterized following macrophage exposure to either PMMA or control polystyrene particles. Temporal release of radiolabeled products by [14C]arachidonate-labeled cells was determined by sequential scintillation counting. Significant dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 29 publications
0
53
0
3
Order By: Relevance
“…Once a membrane is established and an implant is unstable, the situation seems to be very different. Fluid pressure generated by instability has a strong osteolysis-activating effect , and there is also some evidence that wear particles entering the membrane may activate osteoclasts (Horowitz et al 1991, Kadoya et al 1997. Finally, increasing fatigue may be an alternative explanation of continuous migration (Taylor and Tanner 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once a membrane is established and an implant is unstable, the situation seems to be very different. Fluid pressure generated by instability has a strong osteolysis-activating effect , and there is also some evidence that wear particles entering the membrane may activate osteoclasts (Horowitz et al 1991, Kadoya et al 1997. Finally, increasing fatigue may be an alternative explanation of continuous migration (Taylor and Tanner 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Once primary stability is lost and a fibrous membrane formed, micromotion will prevent osseous anchorage from being reestablished. The membrane that ensues may then allow further osteolysis with time, due to fluid pressure effects (Robertsson et al 1997 or possibly effects from particles entering the membrane (Horowitz et al 1991, Kadoya et al 1997. These secondary phenomena may lead to clinical loosening.…”
mentioning
confidence: 99%
“…The absence of these cells in particle-treated cultures indicates that PMMA particles do not induce adherent monocytes to differentiate into macrophages and osteoclasts. Because osteogenic cultures that are not challenged with particles still contain monocyte-macrophages, the absence of these cells in particletreated cultures is most likely due to a cytotoxic effect of PMMA particles 20,21 and not to a physiologic effect of the osteogenic medium. Together, these results demonstrate that the inhibition of osteoprogenitor differentiation is unlikely to be due to inhibitory factors released by particle-activated cells in the heterogeneous bone marrow cell culture.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Various studies have shown the good performance of the alumina ceramic-on-ceramic articular surfaces in terms of frictional behaviour, low annual rates of wear and relatively low reactivity of debris in the periprosthetic tissues, compared with polyethylene wear from metal-polyethylene couples. [15][16][17][18][19][20][21][22][23] Light-microscope studies of membranes around revised ceramic THRs reported sizes of alumina particle of between 1 and 3 m which is similar to the grain size of alumina used for production.…”
mentioning
confidence: 99%